Gender intelligence : breakthrough strategies for increasing diversity and improving your bottom line - Annis, Barbara, 1954-; Merron, Keith (2014)
"Despite forty years of laws, quotas, diversity training, and legal expenses aimed toward equalizing pay, opportunities, and working conditions between the sexes, the glass ceiling remains firmly intact. For too long, companies have played the "numbers game"--attempting to tackle gender imbalance by forcing affirmative action policies and numeric standards on organizations to increase the representation of women in management. Yet, these efforts have rarely been sustained. In this groundbreaking comprehensive analysis, based on more than twenty-five years of in-depth surveys involving 100,000 men and women across dozens of Fortune 500 companies, Barbara Annis and Keith Merron provide a deeper understanding of the multiplicity of forces that have combined to create and perpetuate gender inequality. Gender Intelligence exposes common false assumptions that prevent men and women from successfully performing together at work--myths exacerbated by worn-out theories of gender blindness and sameness thinking. It show how a small but growing number of courageous, leading-edge companies have broken through the barriers to successfully advance women, making the remarkable transformation from compliance to choice--from pressure to preference--and show how it can be done in any business."--
A new conversation. Gender intelligence ; The science behind our gender differences ; Brain science at work ; Breakthrough insights that are transforming companies ; The journey of gender-intelligent companies -- Why gender intelligence is next in the evolution. Past, present, and future ; The gender-intelligent leader -- How gender intelligence affects the organization. Functions, processes, and systems ; The economics of gender diversity ; Gender-intelligent organizations today -- Conditions for success. How to get started.
Includes bibliographical references (pages 241-244) and index.
Keywords: Women employees; Women -- Employment -- Economic aspects; Leadership; Sex role in the work environment